(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Education is the foremost and vital of all the other factors contributing to developing an economy. It provides qualitative and quantitative labor for the further production and development process in the country. The present study scrutinized the development of education in the states of India in 2016-17 and delineated the categories for the state according to their educational development. The study used secondary data compiled by the DISE 2016-17. The Education Development Index (EDI) has been built by applying Factor Analysis on 22 indicators and categorizing the States Inter Quartile Range formula has been used. The study results delineate that states are more developed at Senior Secondary education level than other levels and in case of composite index states such as Puducherry, Delhi, Tamil Nadu, and Mizoram Punjab are highly developed. At the same time, Sikkim, Bihar, Andaman & Nicobar, and Arunachal Pradesh are the states having the lowest EDI. Thus to overcome such differences, proper plans should be made, and there should be an immediate implementation of those plans.